SISTEM APLIKASI PENERBITAN ANGKA PENGENAL IMPOR ( API ) DI DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI JAWA TENGAH (Information Technology and Telematics, 2015)
Abstraction In this study takes the object on the system service application for the issuance of Import Identification Number (API) in the Department of Industry and Trade of the Province of Central Java in the process of publishing and reporting actual import data still using manual systems that cause the lack of effectiveness and efficiency in the process of its activities, it is impact on a relatively long time and allow for errors in the data input process.This study aims to build system new applications that can assist and accelerate the process of publishing services Import Identification Number and reporting actual import data in the Department of Industry and Trade of the Province of Central Java. Based on the analysis, then the auther takes "System Application Publishing Import Identification Number (API) in the Department of Industry and Trade of the Province of Central Java" as the tille of this thesis. From this study produced a web-based application solutions that can help the process of publishing and data processing services imports so that the process becomes more effective and efficient. Keywords: System Applications, Publishing, Import Identification Number